Respuestas

¡La mejor respuesta!
2013-12-06T01:06:14+01:00
A)  3x² = 48  ==>  x² = 48/3  ==>  x² = 16  ==>  x = (+ ó -) raíz_cuadrada(16)

     por lo tanto  x= + 4      ó      x = - 4

b)  x² = 5x   ==>  x² - 5x = 0    ==>  x(x - 5) = 0  ==>  x = 0    ó    x - 5 = 0  ya que un producto se anula si al menos uno de los factores es cero.

así que    x = 0   ó    x - 5 = 0  ==>  x = 5

c)  4x² = - 32x  ==>   4x² + 32x = 0    ==>    4x(x + 8) = 0    ==>    4x = 0    ó
    
     x + 8 = 0

por lo tanto    x = 0/4  ==>  x = 0    ó    x + 8 = 0  ==>  x = - 8

d)  x² - 3x = 3x² - 4x    ==>   3x² - x² - 4x + 3x = 0    ==>    2x² - x = 0    ==>

     x(2x - 1) = 0    ==>    x = 0    ó    2x - 1 = 0  ==>  2x = 1  ==>  x = 1/2